Bimbingan Tahfidz Al- Qur’an Melalui Media Puzzle Dalam Meningkan Motivasi Menghafal Di Madrasah Diniyah Al Musyarrofah - Muhammad Saepul Ulum (Jurnal Bimbingan Penyuluhan Islam, 2022)
This research is motivated by conducting preliminary studies in the field through direct observation and interviews with school principals and tahfidz supervisors from 30 motivated fifth grade students. This is shown by the obedience and presence of the students while participating in the Tahfidz mentoring activities. However, there are still relatively few students who can recite it. This shows that the enthusiasm of students to learn the Qur'an is very low. The purpose of this study was to determine the role of the tahfidz learning process in increasing the motivation to recite the Qur'an for fifth grade students of Madrasah Al-Musyarrofah through the use of educational media. Besides that, it also aims to find out the results of tahfidz learning in terms of increasing motivation to recite through educational media. This research is based on the idea that students' motivation to memorize the Qur'an depends on the media and learning methods given in class. If the supervisor does not have a method in learning, the learning will be monotonous so that students' motivation in memorizing the Qur'an will decrease. While the process of memorizing the Al-Qur'an which is flat without involving a method, is an obstacle for the supervisor to build motivation in students which is the key to success in memorizing the Al-Qur'an. So with the use of methods or media, students' motivation in memorizing the Qur'an is increasing. The method used in this study is a descriptive method and a qualitative approach to find an overview of tahfidz guidance through puzzle media to increase the motivation to memorize the Al-Qur'an. The data collection techniques are carried out by means of observation, interviews and literature study. Based on the research analysis that has been carried out, the application of the media puzzle method to increase students' motivation to memorize the Qur'an is going well. This can be seen by increasing the memorization of verses of the Koran in children. Thus, it can be concluded that the memorization of verses of the Qur'an in fifth grade students of Madrasah Al Musyarrofah has increased during the implementation of the learning model using the game method using puzzle media.